The relationship between organisational climate and organisational innovativeness: Testing the moderating effect of individual values of power and achievement - (:unkn) unknown (Inderscience Publishers, 2017)
This study aimed to investigate the effect of organisational climate on organisational innovativeness and to test the moderating role of manager's individual values of power and achievement. Data were collected from a sample of 312 managerial level employees that represented the innovative companies from different sectors operated in Turkey. Confirmatory factor analysis (CFA) was used to evaluate the construction of the questionnaire. The relationship among organisational climate; organisational innovativeness and individual values were tested applying the structural equation modelling (SEM) technique. The results indicated that individual values had positive influence on organisational innovativeness, but the effect of organisational climate was not significant on organisational innovativeness. Further, the results demonstrated that individual values of power and achievement had positive effect on organisational innovativeness and significantly moderated the relationship between perceived organisational climate and organisational innovativeness. Due to the interpretation of the findings, the concluding remarks were specified, the theoretical and practical implications of the research findings were discussed, and potential future suggestions and limitations were provided. Copyright © 2017 Inderscience Enterprises Ltd.
Keywords: Individual values; Organisational climate; Organisational innovativeness; Power and achievement; SEM; Structural equation modeling